The Levels of Adhesion Molecules in Essential Thrombocythemia - Oktay Bilgir; Ferda Bilgir; Mehmet Calan; Ferlt Sari (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Background: It is known that thrombocytosis is closely related to vascular complications and particularly thrombosis in essential thrombocytemia (ET) cases. The aim of this study is to investigate a possible correlation between adhesion molecules and vascular attacks as well as the relation of these molecules to the platelet count.